The first rule - Crais, Robert (New York : Berkley Books, 2011)
Elvis Cole's taciturn partner, Joe Pike, investigates an attack on former associate Frank Meyer, a one-time mercenary whose family has been murdered by a professional hit crew and who police suspect has been keeping a dangerous secret.
Originally published: New York : G.P. Putnam's Sons, c2010.
Keywords: Pike, Joe (Fictitious character) -- Fiction; Cole, Elvis (Fictitious character) -- Fiction; Married people -- Crimes against -- Fiction; Home invasion -- California -- Westwood -- Fiction; Drug traffic -- California -- Los Angeles -- Fiction; Private investigators -- California -- Los Angeles -- Fiction; Mystery fiction